(untitled) (Global Journal of Human-Social Science, 2016)
National security landscape has undergone an inclusive dynamics through the threat of cross- border migration process. This study aims to discuss the migration of the people of Myanmar, especially the Rohingya’s ethnic to Malaysia. Analysis of non-traditional’s threats interpreting internal security challenge to Malaysians are the main elements of the discussion in this study. Through a qualitative study and validation of accuracy of procedural information, this study argues that three non-traditional’s threats to human trafficking, local colony formation, and cross the border illegally as the underlying impact of migration among the Rohingya. In addition, the pressure of social responsibility on human factors also contributed constraints of national security policy based on the image of Malaysia. Thus, several proposals were discussed to contribute to policy-makers regarding the cross-border migration in Malaysia. The study found that the entry of illegal immigrants/ refugees Rohingya has created problems for the country, through the issue of cross-border illegally and the government had to bear a heavy responsibility to accept Rohingya refugees which they are long-term problems that pose the nontraditional’s threat to the country.